A frozen matrix hybrid optical nonlinear system enhanced by a particle lens. Issue 36 (26th August 2015) - Chen, Lianwei; Zheng, Xiaorui; Du, Zheren; Jia, Baohua; Gu, Min; Hong, Minghui
Abstract : In this work, a Graphene Oxide (GO) nano-sheet and SiO2 micro-bead hybrid system based on a frozen matrix was investigated for its enhanced optical nonlinear performance. Abstract : In this work, a Graphene Oxide (GO) nano-sheet and SiO2 micro-bead hybrid system based on a frozen matrix was investigated for its enhanced optical nonlinear performance. A frozen matrix is a novel approach that hosts the optical nonlinear nano-particles, which combines the strengths from both liquid and solid phase systems for high performance photonic applications. SiO2 micro-beads were used to induce a local field enhancement effect that improved the optical nonlinearity of GO nano-sheets. The nonlinear performance of the hybrid system is several orders higher than the existing GO nano-sheet liquid dispersion. In addition, this frozen matrix and the local field enhancement effect are two facile and versatile methods that can be applied to many types of nano-particle dispersions.